(untitled) (Journal of Engineering, 2026)
Groundwater resources in arid and semi-arid regions are highly sensitive to climate variability, and assessing future water balance conditions is essential for sustainable management. This study evaluates the effect of climate change on the water balance of the Al-Teeb district in southern Iraq under both historical (1993–2023) and future (2031–2050) climate conditions. The analysis was performed with the Thornthwaite-Lerner method, combined with statistically downscaled climate projections produced through Long Ashton Research Station Weather Generator (LARS-WG, v8) that was driven by HadGEM3-GC31-LL GCM for the SSP2-4. 5 scenarios. During the reference period, mean annual precipitation amounted to 178.9 mm/yr, and corrected potential evapotranspiration (PETc) was 2535 mm/yr, resulting in a large annual water deficit (2414 mm/yr) and indicating arid conditions in this region. Future simulations indicate a rise in precipitation (258.4 mm/yr), but a sharper increase in PETc to 4011 mm/yr, resulting in a larger deficit (3853 mm/yr) while the region remains arid. Groundwater recharge, estimated using the coefficient approach, was 8.9 mm/yr in the baseline and 12.9 mm/yr in the future scenario. Although rainfall is projected to increase, the strong evaporative demand severely restricts recharge opportunities. These findings highlight the urgent need for adaptive groundwater management strategies to mitigate intensifying aridity and secure long-term water availability in the Al-Teeb district.